MOBILE COMMERCE: ISU DAN ETIKA DALAM BERBAGAI PERSPEKTIF - Haimi Ardiansyah (VOCATECH: Vocational Education and Technology Journal, 2022)
This paper discusses about mobile commerce (m-commerce) issues and ethics in several perspectives. The objective of this study is to find out the actual issues regarding the availability of m-commerce in various platforms, information quality of m-commerce, security issues of using mobile internet, and usability of mobile commerce. Moreover, the issues are analyzed based on cross-cultural point of view. In addition, the paper also depicts about issue of social and cross-cultural of mobile internet usage  that  have been highly variable between countries without following any single worldwide reasoning or pattern. Variations in adoption and utilization between nations may be happened because of variations in the mobile communication facilities, to the range of m-commerce solutions on offer, to the marketing techniques utilized by companies and to the actual lifestyle of the customers of m-commerce solutions. In essence, the study also identifies about actual information regarding M-Commerce and guide entrepreneurs in doing the online business in future.